Estudo cristalográfico da chalcona fluorada C18H17FO como potencial pesticida - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
Chalcones are substances considered as intermediate precursors of the biosynthetic route of flavonoids and isoflavonoids. They are widely studied compounds due to their wide spectrum of biological activity with pesticide use in agriculture directed to pest control. The knowledge of the structure of these compounds through the arrangement of the atoms in the molecules, aid in the understanding of their chemical, physical and biological properties. The present work considers the structural elucidation of fluorinated chalcone (E) -1- (4-fluorophenyl) -3- (4-isopropylphenyl) prop-2-en-1-one (C18H17FO). The studied compound presents metrics according to the monoclinic centrosimmetric space group P21/n. In addition, the mapping of the intermolecular interactions was made through the surface of Hirshfeld. In this structure, only non-classical intermolecular interactions can be observed. A dimeric system can be verified, being stabilized by hydrogen bonds of type C-H...F, interactions of type C-H...O, besides the hydrophobic C-H...π. The characterization of fluorinated chalcone was significant to increase the structural knowledge of the compound, besides helping to understand the packaging, supramolecular arrangement and future studies of biological activity-structure.
Keywords: Cristalografia; Difração de raios X; Superfície de Hirshfeld; Crystallography; X-ray diffraction; Hirshfeld surface.; CIENCIAS EXATAS E DA TERRA::QUIMICA